2015
DOI: 10.3390/coatings5030488
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Study on the Effect of Spray Parameters on Characteristics of P3HT:PCBM Active Layers Made by Spray Coating

Abstract: This paper is an attempt to elucidate the effects of the important spray characteristics on the surface morphology and light absorbance of spray-on P3HT:PCBM thin-films, used as an active layer in polymer solar cells (PSCs). Spray coating or deposition is a viable scalable technique for the large-scale, fast, and low-cost fabrication of solution-processed solar cells, and has been widely used for device fabrication, although the fundamental understanding of the underlying and controlling parameters, such as sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 48 publications
0
17
1
Order By: Relevance
“…This is in agreement with the result of other reports, which declared that the roughness of spray-on perovskite films increases by increasing the thickness [25]. It is noted that in less-crystalline or amorphous films, such as polymeric films, the correlation between the number of spray passes and roughness may be somewhat different from what was observed here for perovskite films, simply because, in polymeric films, the phenomenon of crystallization dewetting and the formation of large grains is absent or it is insignificant [40]. To fabricate the best functional perovskite film, i.e., lowest roughness and proper thickness with negligible PbI2 impurity, the spraying process was repeated using different passes (40, 70 and 100) on hotplates at the optimum temperature of 150 °C, which yields the best conversion ratio (Figure 8).…”
Section: Resultscontrasting
confidence: 64%
“…This is in agreement with the result of other reports, which declared that the roughness of spray-on perovskite films increases by increasing the thickness [25]. It is noted that in less-crystalline or amorphous films, such as polymeric films, the correlation between the number of spray passes and roughness may be somewhat different from what was observed here for perovskite films, simply because, in polymeric films, the phenomenon of crystallization dewetting and the formation of large grains is absent or it is insignificant [40]. To fabricate the best functional perovskite film, i.e., lowest roughness and proper thickness with negligible PbI2 impurity, the spraying process was repeated using different passes (40, 70 and 100) on hotplates at the optimum temperature of 150 °C, which yields the best conversion ratio (Figure 8).…”
Section: Resultscontrasting
confidence: 64%
“…They found that the absorption of the active layer increases with active layer thickness. Yu Xie et al investigated the effects of thickness on light absorbance of P3HT:PCBM thin-films which is used as an active layer in polymer solar cells (PSCs) [26]. This active material was deposited using spray method.…”
Section: Resultsmentioning
confidence: 99%
“…After deposition, washing the thin film with water or acid treatment is recommended to remove the residual solvents. Reports on spray deposition of Ag NWs [21,22,33,60,61] have demonstrated the workability of this method [62,63].…”
Section: Spray Coatingmentioning
confidence: 99%